Effect of initial quality of oil and thermal processing on oxidation indexes in canned tuna - Sobhan Taerian Esfahani; Nafiseh Zamindar; Yasaman Esmaeili; Samira Sharifian (Applied Food Research)
The content of fatty acids and the ratio of unsaturated and saturated fatty acids are essential parameters for determining the nutritional value of oils. The main objective of this study was to identify the oxidation changes of three vegetable oils (soybean, sunflower, and olive oil) at two qualitative levels in the canned tuna product before and after the thermal process. The progress of oil oxidation was assessed by measuring peroxide value (PV), p-anisidine value (AV), malonaldehyde (MDA) content, Conjugated dienes (CDs), and conjugated trienes (CTs), p-anisidine value, total free acidity, INTOX and TOTOX values. The results indicated that the quality of oil extracted from canned fish changes according to the type of oil (p < 0.01). A decrease in the peroxide value during the thermal process (<2 meq O2/kg oil in olive and soybean oil), indicated that this parameter is not suitable for showing product quality and oxidation progress, lonely. Secondary products of oxidation, in soybean oil under sterilization caused an increase of p-anisidine value (149) but in olive and sunflower oil heating caused a rise of MDA content. Acidity value was an index that increased after heating all types of oil and all types of quality and seemed to be more reliable for determination of the quality of oil in canned tuna (p < 0.01).